A chip assisted immunomagnetic separation system for the efficient capture and in situ identification of circulating tumor cells. Issue 7 (1st March 2016) - Tang, Man; Wen, Cong-Ying; Wu, Ling-Ling; Hong, Shao-Li; Hu, Jiao; Xu, Chun-Miao; Pang, Dai-Wen; Zhang, Zhi-Ling
Abstract : The detection of circulating tumor cells (CTCs), a kind of "liquid biopsy", represents a potential alternative to noninvasive detection, characterization and monitoring of carcinoma. Abstract : The detection of circulating tumor cells (CTCs), a kind of "liquid biopsy", represents a potential alternative to noninvasive detection, characterization and monitoring of carcinoma. Many previous studies have shown that the number of CTCs has a significant relationship with the stage of cancer. However, CTC enrichment and detection remain notoriously difficult because they are extremely rare in the bloodstream. Herein, aided by a microfluidic device, an immunomagnetic separation system was applied to efficiently capture and in situ identify circulating tumor cells. Magnetic nanospheres (MNs) were modified with an anti-epithelial-cell-adhesion-molecule (anti-EpCAM) antibody to fabricate immunomagnetic nanospheres (IMNs). IMNs were then loaded into the magnetic field controllable microfluidic chip to form uniform IMN patterns. The IMN patterns maintained good stability during the whole processes including enrichment, washing and identification. Apart from its simple manufacture process, the obtained microfluidic device was capable of capturing CTCs from the bloodstream with an efficiency higher than 94%. The captured cells could be directly visualized with an inverted fluorescence microscope in situ by immunocytochemistry (ICC) identification, which decreased cell loss effectively. Besides that, the CTCs could be recovered completely just by PBS washing after removal of the permanent magnets. It was observed that all the processes showed negligible influence on cell viability (viability up to 93%) and that the captured cells could be re-cultured for more than 5 passages after release without disassociating IMNs. In addition, the device was applied to clinical samples and almost all the samples from patients showed positive results, which suggests it could serve as a valuable tool for CTC enrichment and detection in the clinic.